Frame of Mind : Viewpoints on Photography in Contemporary Canadian Art. - Campbell, James D.; Baillargeon, Richard; Bérard, Serge; Lamoureux, Johanne; Zapf, Donna; Laframboise, Alain; Solomon-Godeau, Abigail; Simon, Cheryl; Carr-Harris, Ian; Watson, Scott; Walter Phillips Gallery, The Banff Centre School of Fine Arts, Banff (Banff : Walter Phillips Gallery - The Banff Centre for the Arts Banff, 1993)
Alexander, Shelagh ; April, Raymonde ; Arden, Roy ; Blain, Dominique ; Campbell, Kati ; Evergon ; Lewis, Mark ; McEachern, Susan ; Schelle, Susan ; Wallace, Ian
Frame of Mind : Viewpoints on Photography in Contemporary Canadian Art, Walter Phillips Gallery - The Banff Centre for the Arts, Banff, 1993
boek